Spatial Distribution of Euschistus heros (F.) (Hemiptera: Pentatomidae) in Soybean - Souza, L. A. [UNESP]; Barbosa, J. C. [UNESP]; Grigolli, J. F J [UNESP]; Fraga, D. F. [UNESP]; Maldonado, W. [UNESP]; Busoli, A. C. [UNESP] (Springer Nature, 2013)
Soybean bugs are major crop pests that cause significant reduction in harvest yield and influence grain quality. The aim of this study was to verify the spatial distribution of Euschistus heros (F.) (Hemiptera: Pentatomidae) in conventional and transgenic soybean cultivars. The experiment was conducted during the 2010-2011 crop season in UNESP/FCAV, Jaboticabal, SP, Brazil, in two fields of 10,000-m2 area that were subdivided into 100 plots (10 m × 10 m). The cultivars sown were M 7908 RR and its isoline M-SOY 8001. The number of the first to fifth instars and the number of adults were determined. To evaluate insect dispersion in the area, the following indices were used: variance/mean ratio, Morisita index, Green coefficient, and the k exponent of the negative binomial distribution. To study probabilistic models to describe the spatial distribution of the insects, the adjustments of the Poisson and negative binomial distributions were tested. The first to third instars showed aggregated spatial distribution, whereas the fourth and fifth instars, and adults, isolated or grouped, showed variation in the arrangement, ranging from moderately aggregated to randomly dispersed. During the adjustment of probability distributions, the negative binomial distribution model showed adjustment for the first to third instars, fourth and fifth instars, adults, and fourth and fifth instars plus adults. © 2013 Sociedade Entomológica do Brasil.
Keywords: Dispersion; Glycine max; negative binomial; soybean bugs